Mid-term results of a prospective randomised controlled trial comparing large-head metal-on-metal hip replacement to hip resurfacing using patient-reported outcome measures and objective functional task-based outcomes. Issue 5 (September 2021) - Konan, Sujith; Waugh, Charlotte; Ohly, Nick; Duncan, Clive P; Masri, Bassam A; Garbuz, Donald S
Background: The early outcomes of large head-metal-on-metal total hip arthroplasty (MoM THA) are compromised by adverse local tissue reaction to metal debris. This study is the mid-term follow-up of a prospective randomised control trial (pRCT) comparing MoM THA to MoM HR. We sought to answer whether there was a difference between MoM THA and MoM HR at mid-term follow-up in the implant survival; patient-reported outcome measures (PROMs); and when performing objective functional tasks? Methods: A total of 104 patients were studied. Of these 56 had MoM THA (50 male) and 48 had HR (43 male). Mean age at surgery was 52 years in both groups. We reviewed this cohort at mid-term follow-up [minimum 8 years (mean 9 years; range 8–10; SD 0.7)]. PROMs that were completed were OHS, WOMAC, SF-12, and the UCLA. For objective functional task-based outcomes, gait parameters for operated legs were assessed in a subgroup of 17 patients with high UCLA. Results: Revision rate in MoM THA group was 7/56 (12.5%) and in the HR group was 1/48 (2.1%). Overall revision rate at minimum 8-year follow-up was 7.7% (8 of 104 patients). PROMs data comparing MoM THA versus HR showed no difference between the groups. 4 (8.5%) of the non-revised (47) HR patients had WOMAC function or pain score below 70. 3 (6.4%) patients had both pain and function scores <70. In the THA group, 5 (10.2%) of the non-revised (49) patients had WOMAC pain or function scores <70. 3 (6.1%) patients had both pain and function scores <70. The comparison of HA versus THA showed several gait parameters in the HR group to be better but not statistically significant ( p > 0.05 Mann-Whitney U-test). Conclusions: At mid-term follow-up, the revision rate of MoM articulation for THA is high (7.7%), being higher in large head MoM total hips versus resurfacing. Overall probability of 10-year survival is 92.3% (KM analysis, 95% for MoM THA and 98% for HR). The HR group had better functional parameters on gait-based tasks compared to THA group but this difference did not reach statistical significance.